Arizona - Ewa Borzecka (Telewizja Polska, 1998)
In 1990, the 750,000 acre state farm in the Polish village of Zagorki went bankrupt. The socialist dream was over, leaving farm workers out of a job. From a flourishing, thriving community, the village is now reduced to a sad lot of embittered people, whose sole consolation is a small allowance and whose sole dictraction is the oblivion offered by the cheap "Arizona" wine. Consumed by everyone in the village, whether young or old, sick or healthy, even by those who cannot afford to buy bread, "Arizona" has become the trusty remedy against misery, despair, and hunger. Poems have been written about it, and songs praising its virtues are sung in front of the liquor store. The camera mercilessly registers the dismal condition of the houses and streets, and the numerous candid interviews supply a poignant image of the dead-end situation of this remote village.